The current pattern of reconstructive surgery for breast cancer - A. Kh. Ismagilov; A. R. Khamitov; A. S. Vanesyan (ABV-press, 2015)
In Russia, breast cancer (BC) occupies a leading place in the pattern of cancers, the incidence of which is 20.9 %, among the female population; in 2013 there were 60,717 new cases, including women under the age of 40 years (15 %). While considering the history of the development of breast surgery from the operation performed by W. S. Halsted to its technique modified by J. L. Madden and the identification of sentinel lymph nodes, we can observe improved quality of life in patients in reference to the lower rate of the manifestation of lymphedemas. However, patients who have undergone this or that mastectomy are observed to have lower self-appraisal scores, a change in their professional sphere, irritability and apprehensiveness Thus, the decreased rate of the manifestation of lymphedema and obvious postoperative traumatization are not the only components of quality of life in patients with BC. According to the data obtained by E. Frank et al. (1978), G.P. Maguire et al. (1978), and F. Meerwein (1981), removal of the breast itself leads to a woman's loss of femininity, attractiveness, and sexiness, which was also confirmed and reported by L. Aerts et al. (2014). In this connection, classical radical mastectomy begins to give way to organ-sparing treatment. Taking into account that psychotherapy and external prosthetics do not alleviate the above problems and that there are always women with established BC who have contraindications to organ-sparing treatment, breast reconstructive plastic operations arouse more and more interest. Reconstruction of the breast implies restoration of both its shape and contours to be maximally brought closer to its preoperative level. However, with regard to cancer alertness to breast reconstructive surgery, not only aesthetic requirements are imposed. The next step in improving quality of life in patients with BC was the emergence and development of breast-sparing mastectomies, the first point of these operations were skin-sparing radical mastectomies that were first described and performed by B. A. Tothu P. Lappert in 1991. In 1997 G. W. Carlson proposed to classify incisions for skin-sparing mastectomy successfully used to the present day. The investigation conducted by R. M. Simmons et al. (1999) indicated that skin-sparing mastectomy did not result in an increase in the incidence of local recurrences. The types of skin incisions, which were offered by G. W. Carlson in 1997 and used by R. M. Simmons in 1999, imply the preservation of the inframammary crease and a major portion of a skin graft, on the one hand, and the removal of the nipple-areolar complex (NAC), on the other hand, which in turn diminishes the final aesthetic result. B. Gerber et al. were the first to describe NAC preservation for BC. As regards the rate of local recurrences after NAC-sparing mastectomies, the vast majority of investigations performed in the past 10-15 years allude to the fact that NAC involvement is not more than 25 %. A. M. Munhoz in turn proposed a classification of incisions during NAC-saving mastectomies. In spite of all advantages of NAC-sparing mastectomies, their results are not always predictable. Main problems, such as wound healing difficulties or ischemic necrosis, are associated with the larger number of postoperative complications. Transfer of the patient's own flaps does not always presume skin- or NAC-sparing mastectomy, as the possibility exists of preserving the skin on the most transferable flap. However, ruling out a patch symptom during subcutaneous or skin-sparing radical mastectomy considerably improves the aesthetic result of a performed operation. Taking into consideration that the incision types offered by G. W. Carlson and A. M. Munhoz depend on the site of a tumor, the surgical visibility problem is of relevance: visible postoperative scars, a difference in the skin texture, or restored NAC, all cause the women less satisfied. Thus, by achieving good results in restoring the contours, shape, volume, and symmetry of the breast, a visible postoperative scar is the only element that reveals a performed operation for BC.